Kualitas air minum isi ulang pada depot air minum di Kabupaten Manokwari Selatan - Awliya Nur Marhamah; Budi Santoso; Budi Santoso (Cassowary, 2020)
Water is a chemical compound that is very important for the life of human beings and other living things. Refill water is water that undergoes special treatment, among others, the process of chlorination, aeration, filtration and irradiation with ultraviolet light. The objectives of this study were to determine the quality of refill drinking water produced by refill drinking water depots in South Manokwari Regency based on physical, chemical and microbiological variables. The descriptive method was used in this study. Samples of refill drinking water were collected from 6 depots located in South Manokwari Regency. Water samples are taken to the laboratory for chemical, physical and microbiological quality analyzes. Good quality refill drinking water at the kiosk is drinking water produced by depots B and F, while drinking water produced from depot E was quite good.. The refill drinking water treatment process was carried out using the reverse osmosis method, a combination of the reverse osmosis and ultraviolet methods. The quality of refill drinking water in depots B, D, and F meets the quality standard requirements based on Permenkes 2010. E. coli population contained in refill water in depots A, C and F after storage in gallons for 3 days was above the quality standard requirements so it must be boiled before being consumed by humans.